Slovak Republic : 2021 Article IV Consultation-Press Release; Staff Report. (IMF Staff Country Reports; Country Report, 2021)
The Slovak Republic faced the pandemic from a position of strength with fiscal space and comfortable banking sector buffers. Effective policy support, through measures aimed at preserving jobs, providing liquidity support, and ensuring credit supply, have limited the economic fallout. Output is expected to reach pre-crisis level before the end of 2021, but uncertainty is high.